2007
DOI: 10.1562/0031-8655(2002)0760350fditop2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Distribution in Tissues of Phillyrea latifolia L. Leaves as Estimated by Microspectrofluorometry and Multispectral Fluorescence Microimaging¶

Abstract: A new method for detecting the tissue‐specific distribution of flavonoids has been developed by coupling microspectrofluorometry and multispectral fluorescence microimaging techniques. Fluorescence responses of cross sections taken from 1 year old Phillyrea latifolia leaves exposed to full (sun leaves) or 15% (shade leaves) solar radiation in a coastal area of Southern Tuscany were analyzed. Fluorescence spectra of different tissue layers, each normalized at its fluorescence maximum, that were stained or not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 86 publications
2
26
0
Order By: Relevance
“…6B). We note here that (1): cell-wall conjugated phenolics (possibly including flavonoids, as previously reported to occur in another member of the Oleaceae family, Agati et al, 2002) may have contributed in part to F 580 in the mesophyll cells, although to a similar degree in PAR30 and PAR100 leaves (wall-bound phenolics did not substantially differ in differentially irradiated leaves); and (2) the strong F 580 intensity from the abaxial epidermal layers, which also include the leaf surfaces, originates from both the leaf angle (which was steep in PAR100 leaves) and the fluorescence due to flavonoids secreted by the glandular trichomes, which are mostly distributed on the abaxial surface in L. vulgare (Tattini et al, 2005;Agati and Tattini, 2010).…”
Section: Inter-and Intra-cellular Distribution Of 'Antioxidant' Flavosupporting
confidence: 69%
See 1 more Smart Citation
“…6B). We note here that (1): cell-wall conjugated phenolics (possibly including flavonoids, as previously reported to occur in another member of the Oleaceae family, Agati et al, 2002) may have contributed in part to F 580 in the mesophyll cells, although to a similar degree in PAR30 and PAR100 leaves (wall-bound phenolics did not substantially differ in differentially irradiated leaves); and (2) the strong F 580 intensity from the abaxial epidermal layers, which also include the leaf surfaces, originates from both the leaf angle (which was steep in PAR100 leaves) and the fluorescence due to flavonoids secreted by the glandular trichomes, which are mostly distributed on the abaxial surface in L. vulgare (Tattini et al, 2005;Agati and Tattini, 2010).…”
Section: Inter-and Intra-cellular Distribution Of 'Antioxidant' Flavosupporting
confidence: 69%
“…By contrast, wall-bound conjugated phenolics contributed to F 580 , as phenolics, when "associated" with cellular matrixes (and not dissolved in the cellular milieu) are capable of UV-and blue light-induced fluorescence (even auto-fluorescence, McNally et al, 2003;Tattini et al, 2007;Agati and Tattini, 2010). Wall-bound phenolics, which were estimated as reported previously (Agati et al, 2002), differed less than 15% in differentially irradiated leaves.…”
Section: Localization Of Flavonoidssupporting
confidence: 53%
“…The results were same with pteridophytes [41]. The stress environment such as dimmer sunshine would promote the synthesis of flavonoids [47]. Light quality has been found that could alter flavonoid production [4849].…”
Section: Resultsmentioning
confidence: 54%
“…2A). To test if the glandular trichomes secrete flavonoic compounds, plant material was sprayed with 1 % aminoethyldiphenylborinate in methanol (Naturstoffreagenz A, Sigma-Aldrich, St. Louis, USA) (Jork et al 1989) and observed under excitation by blue radiation (450 -490 nm) (Agati et al 2002). In the trichome exudates no fluorescence that could be related to the flavonoids was detected ( Fig.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%